Mitochondrial Fission of Smooth Muscle Cells Is Involved in Artery Constriction. Issue 5 (November 2016) - Liu, Ming-Yu; Jin, Jing; Li, Shan-Liang; Yan, Jie; Zhen, Chang-Lin; Gao, Jin-Lai; Zhang, Yong-Hui; Zhang, Yan-Qiu; Shen, Xin; Zhang, Liang-Shuan; Wei, Yuan-Yuan; Zhao, Yu; et al.
Abstract : Mitochondria are dynamic organelles and continuously undergo fission and fusion processes. Mitochondrial fission is involved in multiple physiological or pathological processes, but the role of mitochondrial fission of smooth muscle cells in artery constriction is unknown. The role of mitochondrial fission of smooth muscle cells in arterial function was investigated by measuring the tension of rat mesenteric arteries and thoracic aorta and by evaluating mitochondrial fission, mitochondrial reactive oxygen species, and cytosolic [Ca 2+ ]i in rat vascular smooth muscle cells. Mitochondrial fission inhibitors mdivi-1 and dynasore antagonized phenylephrine- and high K + –induced constriction of rat mesenteric arteries. Mdivi-1 relaxed phenylephrine-induced constriction, and mdivi-1 pretreatment prevented phenylephrine-induced constriction in mice, rat aorta, and human mesenteric arteries. Phenylephrine- and high K + –induced increase of mitochondrial fission in smooth muscle cells of rat aorta and the increase was inhibited by mdivi-1. Mdivi-1 inhibited high K + –induced increases of mitochondrial fission, mitochondrial reactive oxygen species, and cytosolic [Ca 2+ ]i in rat vascular smooth muscle cells. Prechelation of cytosolic Ca 2+ prevented high K + –induced cytosolic [Ca 2+ ]i increase, mitochondrial fission, and mitochondrial reactive oxygen species overproduction. Mitochondria-targeted antioxidant mito-TEMPO antagonized phenylephrine- and high K + –induced constriction of rat mesenteric arteries. Nitroglycerin and ROCK (Rho-associated protein kinase) inhibitor Y27632, the 2 vasodilators with different vasorelaxant mechanisms, relaxed high K + –induced vasoconstriction and inhibited high K + –induced mitochondrial fission. In conclusion, the mitochondrial fission of smooth muscle cells is involved in artery constriction. Abstract : Supplemental Digital Content is available in the text.